Early Childhood Caries: Expectant Mothers’ Knowledge, Attitude, and Willingness to Treatment - Malini Venugopal; Vinitha Alex; Ektah Khosla; K. Korath Abraham; Arun Roy James; Elsa Thenumkal (Amrita Journal of Medicine)
Background: Early childhood caries (ECC) is one of the most challenging diseases in childhood, which may begin as soon as teeth erupt into the oral cavity. The treatment is invasive, causing physical as well as mental stress not only among children and parents but also among dentists. ECC also places a heavy financial burden on the community. Hence, preventive treatment is considered to be of utmost importance. This study carried out in Kerala aimed to assess expectant mothers’ knowledge, attitude, and willingness to treat early childhood caries. Materials and Methods: A cross-sectional survey was conducted among 150 expectant mothers visiting the outpatient department of a tertiary care hospital. A validated 28-item questionnaire was administered to know mothers’ awareness of the importance of primary teeth and their attitude, willingness, and readiness to initiate preventive oral healthcare for their children. Results: The result showed that around 89.3% were unaware of when to begin tooth brushing, around 78% had no idea that sharing utensils and frequent kissing can transmit cariogenic bacteria, and almost 81.3% of mothers were unaware of the fact that frequent snacking increases the probability of caries. About 82.7% preferred pedodontist for treatment. Conclusion: Expectant mothers have inadequate knowledge about oral health. The study showed that employed mothers had better oral hygiene knowledge than unemployed mothers. However, educated mothers were willing to prevent this through early identification and regular checkups. Clinical Significance: Kerala is a state with almost 100% literacy, but expectant mothers still have inadequate knowledge about the importance of oral health. The most common barrier to poor oral health in children is insufficient information among mothers about practices for preventing dental healthcare-associated problems. Awareness about dental health must be started during pregnancy to initiate prevention as early as possible. Healthcare information provided to expectant mothers can effectively prevent ECC, and education programs targeted at them will have a higher chance of success. Steps to include awareness programs among medical care providers who are in regular contact with the expectant mother are of paramount importance.